Contributions to the ecology of the anomuran mud prawn Upogebia africana (Ortmann) - Hill, Burke J (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1967)
Estuarine ecology in South Africa has progressed in two distinct stages. The first of these was a necessary descriptive phase which documented the general distribution of estuarine animals and recorded the physical conditions within estuaries . This phase has been carried out by the Zoology Department of the University of Cape Town which has made a series of ecological surveys of southern African estuaries. These surveys have provided a vast amount of valuable information which was utilised by Day (1964.) to state some general conclusions about estuarine faunas. The most important of these conclusions is that most of the estuarine fauna is really a quiet water fauna which also occurs in sheltered non-estuarine water. The information gained in this first stage is necessarily general and it can only indicate overall trends or reveal major features of distribution. Further estuary surveys are not justified unless they deal with unique conditions. It is at this point that the second phase of estuarine ecology becomes necessary. This phase involves a detailed investigation of individual species or particular problems. The present investigation falls into this second stage of estuarine ecology and was designed to extend our knowledge of the anomuran mud prawn Upogebia africana (Ortmann). The general estuarine surveys have shown that U. africana is a common inhabitant of many estuaries and sheltered bays along the southern African coast from Langebaan on the West coast to Inhambane on the East coast. However these surveys only revealed and could not explain anomalies in its distribution such as its apparent absence from closed estuaries and from estuaries in the tropics. In addition it was not even certain whether this abundant and widespread animal should really be considered a valid species distinct from a common West Coast prawn Upogebia capensis (Krauss). It was felt that a study of an estuarine species should be based upon a sound knowledge of its distribution, population structure and habitat. Knowledge of the habitat must be gained by studies in the field to establish which facets of the environment are of importance to the species. It was decided on the basis of field observations that temperature and salinity are of prime importance: in limiting the distribution of U. africana and a detailed laboratory study was therefore made of the tolerance of U. africana to these two physical factors. The results of laboratory experiments together with field observations were finally used to interpret the ecology of the species. Most of present day knowledge of crustacean ecology has been gained from a study of European and North American animals and information about southern hemisphere species has lagged behind. It is hoped that the present study will contribute to a wider understanding of Crustacea and that it will lead to further more advanced research on South African marine and estuarine animals
Keywords: Decapoda; Shrimps